KOORDINASI KEPOLISIAN DAN DINAS PERHUBUNGAN DALAM PENERTIBAN BECAK MOTOR DI KOTA MAKASSAR - Qamal . (Jurnal Ilmiah Ilmu Administrasi Publik, 2016)
Bentor is a means of transportation that has the ability to reach all areas of the city / countryside, travel time and operation, and affordable cost by the community, but the presence of bentor in Makassar, which is now starting to cause overlapping routes between different types of public transport motors. Lack of regulation in the enforcement of Law No. 22 of 2009 About Traffic and Road Transportation and the Mayor of Makassar Regulation number 22 of 2012 concerning the operational control bentor vehicles, is expected to be in control of the main road transport user motor tricycles.